Airport Environment and its influence on Traveller Emotions, Perceived Quality and Revisit - Yerimou, Pantelitsa; Themistocleous, Christos (My University, 2023)
Summary Statement The paper examines the experience journey of travellers at airports by examining both physical and human-related factors of the servicescape. More precisely, how social variables influence travellers' perceived quality and evoked emotions as predecessors of airport satisfaction. Consequentially, we examine desired traveller intentions in relation to WoM and airport revisit. This is the first attempt to synchronise the human-related servicescape of airports with perceived quality, emotions and revisit.
Keywords: Airport Atmospherics; Servicescape; Emotions; Sense of Place; Traveller Studies; Customer Experience